2018
DOI: 10.1016/j.scitotenv.2018.06.322
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil organic carbon stocks of two cities, New York City and Paris

Abstract: In cities, the strong heterogeneity of soils, added to the lack of standardized assessment methods, serves as a barrier to the estimation of their soil organic carbon content (SOC), soil organic carbon stocks (SOCS; kgC m) and soil organic carbon citywide totals (SOCCT; kgC). Are urban soils, even the subsoils and sealed soils, contributing to the global stock of C? To address this question, the SOCS and SOCCT of two cities, New York City (NYC) and Paris, were compared. In NYC, soil samples were collected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 28 publications
4
42
2
Order By: Relevance
“…In contrast, green space management in Paris may help to increase SOC stock in open soil [75]. However, researchers of urban forest soil organic carbon need to learn more from the research experience of natural forest soil and carry out more systematic and comprehensive research in the world [76].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, green space management in Paris may help to increase SOC stock in open soil [75]. However, researchers of urban forest soil organic carbon need to learn more from the research experience of natural forest soil and carry out more systematic and comprehensive research in the world [76].…”
Section: Discussionmentioning
confidence: 99%
“…Cambou et al ( 2021 ) consider urban area soil organic carbon stock mainly depends on whether the soil is sealed or not. Carbon entry into sealed soils is practically impossible (Cambou et al, 2021 ), although Cambou et al ( 2018 ) mention the importance of analyzing subsoil organic carbon storage, in urban sealed soils because total amount is relevant. In fact, approximately 69% of carbon storage in a citywide related to greenspace soil, 13% on sealed soil and 18% on vegetation (Edmondson et al, 2012 ).…”
Section: Healthy Soilmentioning
confidence: 99%
“…Consequently, this paper provides a compilation of their proposals: Strategies to enhance policy, sustainable soil management practices (Cambou et al, 2021 ; Montanarella & Panagos, 2021 ; Tresch et al, 2018a , 2018b ) and direct production processes towards sustainable models (EC, 2020a ). In addition, seems to be a need for addressing the development of globalized regulations for soil protection, for using waste to formulate Technosols, and for standardizing assessment methods (Akande et al, 2019 ; Cambou et al, 2018 ). Authors agree on the requirement of expanding research on analyzing urban soil quality, to assess their level of ecosystem functioning as a service provider (Paradelo et al, 2020 ; Tresch et al, 2018a ), and because additional studies can help to understand links between soils and health (Brevik et al, 2020 ; Fergusson, 2017 ).…”
Section: Europe Green Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of impervious surface expansion on soil carbon storage has been studied from two perspectives. Some studies revealed the differences in SOC storage between sealed soils and surrounding greenspace soil at the sample site scale [14,[19][20][21][22][23], and others have used spatially explicit models driven by land cover change and/or other multiple environmental covariates to analyze the total SOC loss and its spatial and/or temporal variability at regional, national and even global scales [24][25][26][27][28]. These models provide a powerful and effective tool for presenting carbon changes in space and time.…”
Section: Introductionmentioning
confidence: 99%